Crop insurance as a risk management tool in agriculture: The case of silk farmers in northern Iran. (May 2017) - Farzaneh, Majid; Allahyari, Mohammad S.; Damalas, Christos A.; Seidavi, Alireza
Highlights: Factors affecting the adoption of silkworm insurance were explored in northern Iran. The low indemnity rate paid was reported as the main problem of insurance programs. Several farmers (35.6%) were willing to pay for insurance only at indemnity reception. High income and small distance of affiliates from the farms favored insurance adoption. Income from sources other than silk farming discouraged insurance adoption. Abstract: Crop insurance is an important risk coping mechanism in agriculture, but its role in the sense of security has not been yet institutionalized in small farmers' culture. Farmers' preferences and factors affecting the adoption of silkworm insurance were explored in Guilan Province of northern Iran. Over half of the farmers (59.5%) mentioned the low indemnity rate paid by insurance companies as the main problem of insurance services. In addition, the long period of indemnity payment was reported as another major problem of insurance services. A sizeable proportion of the farmers (35.6%) were willing to pay for insurance only at indemnity reception. Most farmers (79.4%) had a risk-taking propensity. Informing silk farmers about damage assessment schedules and about indemnity payment in a timely manner were the most important factors rated by the farmers for insurance adoption. High income and small distance of insurance affiliates from the silk farms was associated positively with insurance adoption. By contrast, income from sources other than silk farming was associated negatively with insurance adoption. The study provides baseline data on farmers' stated preferences and willingness to pay for silkworm insurance, filling a knowledge gap in farmers' behaviour towards insurance adoption. It also answers the question of what drives farmers to adopt insurance schemes for protection of silkworm raising in the area of northern Iran. The information provides useful policy insights on the development of silkworm insurance as a financial facet of a risk mitigation strategy in northern Iran or in other areas where silkworm raising exists and offers insights on what is desirable for silk farmers as far as provision of silkworm insurance is concerned. To improve insurance adoption by silk farmers, it is important to have a fair premium proportional to farmers' income and to pay indemnity to the damaged insured farmers in a timely manner.